The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.2469/faj.v72.n4.9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Management Design on the Portfolio Concentration and Performance of Mutual Funds

Abstract: T he economic role of actively managed equity mutual funds is to delegate the stock selection decisions of individual investors to professional fund managers. The general belief is that these fund managers can generate abnormal returns relative to passive investment strategies. There is an ongoing debate among academics regarding whether actively managed funds outperform passive mutual funds or index funds. Many studies have found that active fund managers do not outperform the market-for example, Wermers (200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 26 publications
(40 reference statements)
1
15
0
Order By: Relevance
“…Cremers and Petajisto (2009) showed that funds with the highest active share tend to outperform their benchmarks significantly. Goldman, Sun, and Zhou (2016) found that mutual funds with higher withinsector concentration perform better than those with more diversification and less active risk. Cremers and Curtis (2015) made a strong implicit case for high-active-risk strategies by showing that the fees charged by "closet index funds" are unjustified.…”
Section: Prior Research On Excess Diversificationmentioning
confidence: 99%
“…Cremers and Petajisto (2009) showed that funds with the highest active share tend to outperform their benchmarks significantly. Goldman, Sun, and Zhou (2016) found that mutual funds with higher withinsector concentration perform better than those with more diversification and less active risk. Cremers and Curtis (2015) made a strong implicit case for high-active-risk strategies by showing that the fees charged by "closet index funds" are unjustified.…”
Section: Prior Research On Excess Diversificationmentioning
confidence: 99%
“…Investment portfolios often contain high numbers of holdings or securities, with US mutual funds typically holding between 40 and 120 stocks [SS05]. More recent work suggests that these numbers have increased, with a mean of 144 and a standard deviation of 271 stocks held [GSZ16]. The ability to visualise a substantial number of pairwise correlations concurrently is therefore of particular interest.…”
Section: Related Workmentioning
confidence: 99%
“…Using pre- calculated layouts (to gauge the underlying rendering engine's performance), the largest test dataset was animated at an average frame rate of 65.7fps. Extrapolating from the performance on the largest test data set, the frame rates reported should be achievable for approximately 85% of investment portfolios, assuming that portfolio sizes are normally distributed and that estimates from Goldman et al [GSZ16] generalise.…”
Section: Scalability and Layout Quality Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite longstanding conventional financial advice to minimize idiosyncratic risk by holding well-diversified portfolios (c.f., McKay et al, 2018), several studies document that both individuals and investment funds concentrate their trades and holdings in certain firms or industries (Brands et al, 2005;Baks et al, 2006;Goldman et al, 2016). Researchers have offered several reasons, including reducing investment information overload (Simon 1972;Agnew andSzykman, 2004: Garvey et al, 2017), possessing an information advantage (Lee and Rahman, 1991;Kacperczyk et al, 2005;Hiraki et al, 2015), and behavioral biases like familiarity (Pool et al, 2012) or overconfidence (Goetzmann and Kumar, 2008), for why individuals and funds would concentrate investment activity and holdings.…”
Section: Introductionmentioning
confidence: 99%